2000
DOI: 10.1038/sj.onc.1203426
|View full text |Cite
|
Sign up to set email alerts
|

Prostate stem cell antigen (PSCA) expression increases with high gleason score, advanced stage and bone metastasis in prostate cancer

Abstract: Prostate stem cell antigen (PSCA) is a recently de®ned homologue of the Thy-1/Ly-6 family of glycosylphosphatidylinositol (GPI)-anchored cell surface antigens. PSCA mRNA is expressed in the basal cells of normal prostate and in more than 80% of prostate cancers. The purpose of the present study was to examine PSCA protein expression in clinical specimens of human prostate cancer. Five monoclonal antibodies were raised against a PSCA-GST fusion protein and screened for their ability to recognize PSCA on the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
357
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(380 citation statements)
references
References 31 publications
18
357
1
4
Order By: Relevance
“…This is particularly noteworthy given that PSCA has been shown to be expressed at low levels in some normal tissues. 9,25 Pancreatic cancer remains the fourth leading cause of cancer-related mortality in the USA with a 5-year overall survival of <5%. 26 More than 53,070 patients are diagnosed annually, and an estimated 41,780 individuals die from this disease each year.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly noteworthy given that PSCA has been shown to be expressed at low levels in some normal tissues. 9,25 Pancreatic cancer remains the fourth leading cause of cancer-related mortality in the USA with a 5-year overall survival of <5%. 26 More than 53,070 patients are diagnosed annually, and an estimated 41,780 individuals die from this disease each year.…”
Section: Discussionmentioning
confidence: 99%
“…This 123-aa type 1 membrane protein has a high tissue specificity and is expressed on more than 85% of CaP specimens, with expression levels increasing with higher Gleason scores and androgen independence. [11][12][13] Several PSCA-derived, HLA-A*0201 restricted peptides have been identified that may be recognized by antigen-specific T cells in vitro. 14,15 Since PSCA is not shedded from the cell membrane, we hypothesized that it may be the most promising CaP-associated antigen for DC-based immunization.…”
mentioning
confidence: 99%
“…Preliminary analysis of archival specimens showed a high percentage of positive staining with an antisense RNA probe for samples, showing overt cancer pathology or indications of high grade PIN, while corresponding normal sections stained weakly (Reiter et al, 1998). Follow-up work using a series of monoclonal antibodies report that an expanded clinical study showed a strong correlation of increased PSCA expression with higher Gleason grade and bone metastasis (Gu et al, 2000). This work indicated that expression was also detected in secretory epithelial cells possibly as a carryover during differentiation of basal into secretory cell populations.…”
Section: Prostate Stem Cell Antigen (Psca)mentioning
confidence: 99%